IIT JEE 1983 Maths - 'Adapted' - FIB to Single-Digit Integer Q7

Geometry Level 4

Let the points of intersection of the line 4 x 3 y 10 = 0 4x-3y-10=0 and the circle x 2 + y 2 2 x + 4 y 20 = 0 x^2+y^2-2x+4y-20=0 be ( a 1 , a 2 ) (a_1,\ a_2) and ( a 3 , a 4 ) (a_3,\ a_4) .

Find 5 + i = 1 4 a i 5 5+\left \lfloor \dfrac {\sum_{i=1}^4a_i}5 \right \rfloor .

Notation: \lfloor \cdot \rfloor denotes the floor function .


In case you are preparing for IIT JEE, you may want to try IIT JEE 1983 Mathematics Archives .


The answer is 4.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

3 solutions

The circle equation can be simplified to ( x 1 ) 2 + ( y + 2 ) 2 = 5 2 (x - 1)^{2} + (y + 2)^{2} = 5^{2} , which describes a circle with center ( 1 , 2 ) (1,-2) and radius 5 5 . Now as ( 1 , 2 ) (1,-2) lies on the line 4 x 3 y 10 = 0 4x - 3y - 10 = 0 , this line will intersect the circle at opposite ends of a diameter, so ( 1 , 2 ) (1,-2) will be the midpoint of ( a 1 , a 2 ) (a_{1}, a_{2}) and ( a 3 , a 4 ) (a_{3}, a_{4}) . Thus

( a 1 + a 3 2 , a 2 + a 4 2 ) = ( 1 , 2 ) a 1 + a 3 = 2 , a 2 + a 4 = 4 a 1 + a 2 + a 3 + a 4 = 2 \left(\dfrac{a_{1} + a_{3}}{2}, \dfrac{a_{2} + a_{4}}{2}\right) = (1, -2) \Longrightarrow a_{1} + a_{3} = 2, a_{2} + a_{4} = -4 \Longrightarrow a_{1} + a_{2} + a_{3} + a_{4} = -2 .

The given expression then evaluates to 5 + 2 5 = 5 + ( 1 ) = 4 5 + \lfloor \dfrac{-2}{5} \rfloor = 5 + (-1) = \boxed{4} .

Meera Somani
Mar 3, 2017

I am better than kushagra juneja, Understand u, I am in class 10 and solved this problem in 2 min, so just give me cheers We get x=3y+10/4(hahah) Then a eq in y =y^2+4y-12=0 So answer =5+-0.4=5-1=4 Understand all u idiots

Why the... anger/language/excitement?

Shubhamkar Ayare - 4 years, 2 months ago

Y = 4 X / 3 10 / 3. s u b s t i t u t i n g i n ( X 1 ) 2 + ( X + 2 ) 2 = 25 , 9 ( X 1 ) 2 + 16 ( X 1 ) 2 = 25 9. ( X 1 ) 2 = 9 , . . . a n d . . X = 2 , 4. Y = 6 , 2.. ( a 1 , . . . a 4 ) = ( 2 , 6 , 4 , 2 ) . S o 5 + ( 2 ) + ( 6 ) + 4 + 2 5 = 5 1 = 4. Y=4X/3 -10/3. ~ substituting~ in~ (X- 1)^2+(X+2)^2=25,\\ 9*(X- 1)^2+16(X-1)^2=25*9.\\ \therefore~ (X-1)^2=9,...and..X= -2,4. \\ Y= -6, 2..\\ (a_1, . . .a_4)=(-2, -6, 4, 2).\\ So~5+\lfloor \dfrac{(-2)+(-6)+4+2 } 5 \rfloor=5-1=\huge 4.

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...